2021
DOI: 10.1016/j.jaci.2020.12.626
|View full text |Cite
|
Sign up to set email alerts
|

Tick peptides evoke itch by activating MrgprC11/MRGPRX1 to sensitize TRPV1 in pruriceptors

Abstract: Background: Tick bites severely threaten human health because they allow the transmission of many deadly pathogens, including viruses, bacteria, protozoa, and helminths. Pruritus is a leading symptom of tick bites, but its molecular and neural bases remain elusive. Objectives: This study sought to discover potent drugs and targets for the specific prevention and treatment of tick bite-induced pruritus and arthropod-related itch.Methods: We used live-cell calcium imaging, patch-clamp recordings, and genetic abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…IPDef1 initiated itch through activating MrgprC11/X1 to sensitize downstream ion channel TRPV1 on dorsal root ganglion neurons. Intriguingly, IPDef1 was also reported to trigger MrgprB2/X2 expressed on mast cells, leading to inflammatory cytokine release and provoking acute inflammation in mice [ 90 ]. These new findings extend the function of tick defensins to itch induction, which provides the basis for the precaution and treatment of pruritus caused by the stings or bites of arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…IPDef1 initiated itch through activating MrgprC11/X1 to sensitize downstream ion channel TRPV1 on dorsal root ganglion neurons. Intriguingly, IPDef1 was also reported to trigger MrgprB2/X2 expressed on mast cells, leading to inflammatory cytokine release and provoking acute inflammation in mice [ 90 ]. These new findings extend the function of tick defensins to itch induction, which provides the basis for the precaution and treatment of pruritus caused by the stings or bites of arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that patients who received Ruxolitinib had a faster clinical and chest CT improvement and displayed significantly decreased levels of cytokines compared to control group. Moreover, no deaths were recorded in the Ruxolitinib receiving group (n = 20) while three patients died due to respiratory failure in the control group (n = 21) [ 94 ]. Another JAKi, Baricitinib has been suggested to be of therapeutic use against SARS-CoV-2 [ 95 ].…”
Section: Anti-il-6 Agents: Therapeutic Targets For Covid-19 Infectionmentioning
confidence: 99%
“…Many of the Mrgprs exhibited preferential distribution exclusively in peripheral sensory neurons. Several of the Mrgprs have been identified to be receptors for itch and pain, including MrgprA3, MrgprC11, and MrgprD [33,51]. In this study, we screened the gene expression of all members of the Mrgprs family in DRG from ACD model mice by RNA-seq and found that Mrgpra3, Mrgprc11, and Mrgprd showed significant upregulation.…”
Section: Discussionmentioning
confidence: 97%